How democratization benefits brokers: a comparison of Mexico City and Khartoum. Issue 1 (2nd January 2020) - Denissen, Ingeborg
ABSTRACT: How does urban brokerage differ in patronage democracies and electoral authoritarian regimes? This article answers this question by providing in-depth comparison of Mexico City and Khartoum, two cities in which electoral competitiveness differs starkly. In both cities, brokers play fundamentally similar functions connecting residents and the state, and mobilizing similar abilities to deliver services for the urban poor. But there is one fundamental difference: brokered relationships between the state and poor people are competitive in Mexico City, whereas in Khartoum they are not. Due to the democratic opening that has unfolded in Mexico since the early 2000s, there are now multiple avenues through which brokers can access state resources. These multiple avenues, and the political competition over the resources they provide, produces multipolar brokerage: brokers can choose between different political patrons and play them off against each other. In electoral authoritarian Khartoum, by contrast, brokerage patterns are unipolar: all avenues lead to a single power source – the ruling party. In comparing urban politics in the two settings, the article concludes that democratization has strengthened brokers in Mexico City, providing them with greater bargaining power and the ability to threaten to take their clienteles to rival patrons.